1996
DOI: 10.1039/p29960001497
|View full text |Cite
|
Sign up to set email alerts
|

Solute–solvent and solvent–solvent interactions in binary solvent mixtures. Part 3. The ET(30) polarity of binary mixtures of hydroxylic solvents

Abstract: II rn 3 7 i Solute-solvent and solvent-solvent interactions in binary solvent mixtures. Part 3. The ET(30) polarity of binary mixtures of hydroxylic solvents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 24 publications
6
114
0
3
Order By: Relevance
“…The k exp value in the mixture is nearly 6% higher than the rate constant value in pure 1-PrOH. This difference is close to the experimental error and makes it possible to neglect a preferential solvation of the 2a molecule by the intersolvent species proposed by Ortega et al in 1996 [2]. In general, the peroxide molecules decompose faster in a mixture containing 1-PrOH than in pure acetone.…”
Section: Decomposition Of Pinacolone Cyclic Diperoxide (2c) In Pure Smentioning
confidence: 75%
See 2 more Smart Citations
“…The k exp value in the mixture is nearly 6% higher than the rate constant value in pure 1-PrOH. This difference is close to the experimental error and makes it possible to neglect a preferential solvation of the 2a molecule by the intersolvent species proposed by Ortega et al in 1996 [2]. In general, the peroxide molecules decompose faster in a mixture containing 1-PrOH than in pure acetone.…”
Section: Decomposition Of Pinacolone Cyclic Diperoxide (2c) In Pure Smentioning
confidence: 75%
“…The reactivity rises up to a value close to that obtained in the pure alcohol when the 1-propanol mole fraction in the binary solvent mixtures is 0.7. This solvent system was considered as a synergetic mixture [2] • C was carried out in pure acetone, pure 1-propanol, and in their binary mixtures (Table III). The k exp values increase in binary mixtures containing 1-propanol up to the highest value in pure alcohol (k prop /k acet = 3.23).…”
Section: Solvent Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…By means of the application of a five-parameter model [two preferential solvations and three E T (30) parameters] a good quantitative description of over 70 binary solvent mixtures was possible. 18 In this paper, we present a description of the solvatochromism in binary solvent systems from the position of the solute, i.e. solvatochromic indicator, using our original model.…”
Section: Introductionmentioning
confidence: 99%
“…The Skwierzyński-Connors model was tested by Rosés and co-workers [16][17][18] using over 100 binary solvent mixtures, including mixtures showing synergetic properties (mixtures of trialkyl phosphates, dimethyl sulfoxide, acetonitrile and nitromethane with chloroform, alcohols and water). With the last-mentioned mixtures, it was observed that increasing the temperature decreases the intensity of the synergetic effect, 17 indicating the thermal decomposition of the relevant solvent-solvent complexes.…”
Section: Introductionmentioning
confidence: 99%